Mycophenolate mofetil vs. cyclophosphamide-based induction regimens for lupus nephritis: outcomes at a tertiary care centre in Lahore, Pakistan - Saeed, Muhammad Ahmed; Asadullah Khan; Faiza Naeem; Nighat Mir Ahmad (Journal of the Pakistan Medical Association, 2024)
Objective: To compare the efficacy of mycophenolate mofetil with intravenous cyclophosphamideas induction therapy in lupus nephritis. Method: The observational, prospecrive, cohort study was conducted at the Rheumatology Department of Fatima Memorial Hospital, Lahore, Pakistan, from July 2016 to June 2019, and comprised lupus nephritis patients. For induction therapy, the patients were assigned at the discretion of the treating rheumatologist to mycophenolate mofetil group MMF, and intravenous cyclophosphamide group CYC. The later group was further divided into NIH subgroup that received the therapy as per the protocol of the National Institutes of Health, and ELNT subgroup which recived the therapy as per the Euro Lupus Nephritis Trial protocol. Maintenance therapy in all groups was mycophenolate mofetil. Tacrolimus was added in case of non-response. The outcome was the achievement of complete renal response at 6, 12 and 24 months. Data was analysed using SPSS 26. Results: Of the 131 patients, 126(96.2%) were females. The overall mean age was 27±7.7 years. There was 58(44.2%) patients in group MMF and 73(55.7%) in group CYC, which had subgroup NIH 46(63%) and subgrpup ELNT 27(37%). The complete renal response rates at 6, 12, and 24 months were 22 (43.1%), 35 (71.4%), and 40(83.3%) for group MMF; 5(12.5%), 9(22%) and 24 (58.5%) for subgroup NIH, and 6(26.1%), 8(36.4%) and 14(63.6%) for subgroup ELNT. Group MMF outcomes were significantly better than the rest (p<0.05). Conclusion: Mycophenolate mofetil induction therapy was more effective than intraveenous cyclophosphamide in terms of achieving remission at 6, 12 and 24 months. Key Words: Systemic lupus erythematous, Lupus nephritis, Mycophenolate mofetil, Cyclophosphamide.